2019
DOI: 10.1038/s41598-018-38106-0
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Thermal Transport Properties of Graphene Paper by Structural Engineering

Abstract: As a two-dimensional material, graphene has attracted increasing attention as heat dissipation material owing to its excellent thermal transport property. In this work, we fabricated sisal nanocrystalline cellulose/functionalized graphene papers (NPGs) with high thermal conductivity by vacuum-assisted self-assembly method. The papers exhibit in-plane thermal conductivity as high as 21.05 W m−1 K−1 with a thermal conductivity enhancement of 403% from the pure cellulose paper. The good thermal transport properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 59 publications
2
10
0
Order By: Relevance
“…The component areas were constrained to correspond to the chemical structure of the polymer repeat units. In the HR spectra of the pristine PL layer, the component peak maxima located at 284.9 eV (aromatic C sp 2 ), 285.3 eV (aliphatic C sp 3 ), 286 eV (C-N sp 3 ), and 288.5 eV (O=C-N) are in good agreement with the positions reported in the literature for the corresponding groups [68][69][70]. The peak at approximately 287 eV can be assigned to the shake-up excitations associated with the aromatic C sp 2 .…”
Section: Copolymersupporting
confidence: 88%
“…The component areas were constrained to correspond to the chemical structure of the polymer repeat units. In the HR spectra of the pristine PL layer, the component peak maxima located at 284.9 eV (aromatic C sp 2 ), 285.3 eV (aliphatic C sp 3 ), 286 eV (C-N sp 3 ), and 288.5 eV (O=C-N) are in good agreement with the positions reported in the literature for the corresponding groups [68][69][70]. The peak at approximately 287 eV can be assigned to the shake-up excitations associated with the aromatic C sp 2 .…”
Section: Copolymersupporting
confidence: 88%
“…Exploiting a vacuum-assisted self-assembly technique, Ren et al 172 engineered thermal transport properties via noncovalent functionalized graphene with NCC. Favorable hydrogen bond association between NCC and functionalized graphene papers (NPGs) endowed excellent thermal properties that is, as high as in-plane TC to 21.05 W m −1 K −1 , good TC over several heating/cooling cycles as well as superior efficacy as an effective heat spreader, Figure 14a−d. A comparison reveals its superiority over a number of composite materials aiming to thermal applications.…”
Section: Emerging Applications Of Nanocellulose-graphene Based Compos...mentioning
confidence: 99%
“…As graphene has a very high in-plane 3000 W/(m·K) conductivity, it is a potential filler in polymeric and epoxy hosts for increased thermal and electrical conductivity; the out-of-plane conductivity of graphene-stack is only 5 W/(m·K) [ 4 ]. Composites that use graphene as the filler, it was previously shown that the thermal conductivity is increasing linearly with its weight percentage (up to 30 wt% before saturation), and in the case of NC-paper with 10 wt% of graphene, reached high 25 W/(m·K) values [ 5 ].…”
Section: Introductionmentioning
confidence: 99%